Combined effects of Olaparib and DNA damage inducing therapies in a zebrafish xenograft model of triple negative breast cancer - Varanda, Ana Beatriz Abreu (2020)
Tese de mestrado, Biologia Molecular e Genética, Universidade de Lisboa, Faculdade de Ciências, 2019